Fine Tuning Non-invasive Respiratory Support to Prevent Lung Injury in the Extremely Premature Infant - Glaser, Kirsten; Speer, Christian P.; Wright, Clyde J. (Frontiers in Pediatrics, 2020)
Within the last decades, therapeutic advances, such as antenatal corticosteroids, surfactant replacement, monitored administration of supplemental oxygen, and sophisticated ventilatory support have significantly improved the survival of extremely premature infants. In contrast, the incidence of some neonatal morbidities has not declined. Rates of bronchopulmonary dysplasia (BPD) remain high and have prompted neonatologists to seek effective strategies of non-invasive respiratory support in high risk infants in order to avoid harmful effects associated with invasive mechanical ventilation. There has been a stepwise replacement of invasive mechanical ventilation by early continuous positive airway pressure (CPAP) as the preferred strategy for initial stabilization and for early respiratory support of the premature infant and management of respiratory distress syndrome. However, the vast majority of high risk babies are mechanically ventilated at least once during their NICU stay. Adjunctive therapies aiming at the prevention of CPAP failure and the support of functional residual capacity have been introduced into clinical practice, including alternative techniques of administering surfactant as well as non-invasive ventilation approaches. In contrast, the strategy of applying sustained lung inflations in the delivery room has recently been abandoned due to evidence of higher rates of death within the first 48 h of life.